HUBUNGAN KUALITAS TIDUR DAN AKTIVITAS FISIK DENGAN TINGKAT KEBUGARAN FISIK DI ERA PANDEMI COVID-19 - Muhammad Aminuddin; Sholichin Sholichin; Siti Rahmadhani; Enda Maimia (Husada Mahakam, 2022)
Good physical fitness is needed to ensure the continuity of education, especially during the Covid-19 pandemic which requires students to do online learning. This study aims to analyze the relationship between sleep quality and physical activity with fitness levels in college students during the Covid-19 pandemic. This study used a descriptive-analytic study method with a cross-sectional design using 228 respondents. Sleep quality was measured using the Pittsburg Sleep Quality Index (PSQI) and physical fitness level were measured using a questionnaire. The data were analyzed using the SPSS Chi-Square statistical test. The results showed good sleep quality in 82 people (36%) and 146 people (64%). The level of physical fitness of respondents is very fit 15 people (6.6%), fit 46 people (20.2%), quite fit 119 people (52.2%) and less fit and not fit 17.1% and 3 respectively,9%. The results of the statistical test of the relationship between sleep quality and physical fitness level obtained p-value = 0.019, which means that there is a significant relationship. There is a significant relationship between sleep quality and student fitness levels during the Covid-19 pandemic.